2005
DOI: 10.1002/mus.20385
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N‐acetylcysteine on glutathione oxidation and fatigue during handgrip exercise

Abstract: Fatigue of hand and forearm muscle groups can limit task performance by astronauts wearing space suits. Countermeasures to delay fatigue would therefore be useful to the space program. N-acetylcysteine (NAC) has been shown to inhibit fatigue during other tasks so we tested its effects during handgrip exercise. Volunteers practiced isometric handgrip maneuvers until performance was reproducible over three successive sessions (baseline). Performance then was retested after ingesting NAC (150 mg.kg(-1)) or saline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
122
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(136 citation statements)
references
References 35 publications
9
122
1
4
Order By: Relevance
“…Moreover, other studies have reported increases in F 2 -isoprostanes (the reference biomarkers of lipid peroxidation) in plasma and decreases in reduced glutathione (GSH; a valid biomarker of the redox state) in erythrocytes after the same 30s cycling test (Groussard et al, 2003a;Groussard et al, 2003b; Cuevas et al, 2005; Cooke et al, 2008;Arent et al, 2010) (Fig.2). Similarly, several studies have reported increases in reactive species production determined by EPR in whole blood (Peters et al, 2006) and changes in the redox couple of reduced glutathione and oxidized glutathione (glutathione disulfide; GSSG) toward a more oxidized redox potential after isometric handgrip exercise (at 50% of maximal voluntary contraction to exhaustion) lasting from 84 to 170s (Matuszczak et al, 2005;Steinberg et al, 2006). Based on this evidence, it seems that even very short isometric exercise activating a relatively small muscle mass is able to increase reactive species production and induce oxidative stress systemically.…”
mentioning
confidence: 89%
“…Moreover, other studies have reported increases in F 2 -isoprostanes (the reference biomarkers of lipid peroxidation) in plasma and decreases in reduced glutathione (GSH; a valid biomarker of the redox state) in erythrocytes after the same 30s cycling test (Groussard et al, 2003a;Groussard et al, 2003b; Cuevas et al, 2005; Cooke et al, 2008;Arent et al, 2010) (Fig.2). Similarly, several studies have reported increases in reactive species production determined by EPR in whole blood (Peters et al, 2006) and changes in the redox couple of reduced glutathione and oxidized glutathione (glutathione disulfide; GSSG) toward a more oxidized redox potential after isometric handgrip exercise (at 50% of maximal voluntary contraction to exhaustion) lasting from 84 to 170s (Matuszczak et al, 2005;Steinberg et al, 2006). Based on this evidence, it seems that even very short isometric exercise activating a relatively small muscle mass is able to increase reactive species production and induce oxidative stress systemically.…”
mentioning
confidence: 89%
“…While a direct cause and effect relationship has not been established, indirect evidence suggests that oxidative stress limits exercise capacity and may modulate exercise-induced adaptive signalling. ROS-selective antioxidants have been utilised to significantly increase sub-maximal exercise time to exhaustion but do not appear to promote any delay in fatigue at high-intensity workloads in human skeletal muscle in vivo (Medved et al 2003;Medved et al 2004;Matuszczak et al 2005). Therefore, prolonged endurance exercise appears to be a stimulus more likely to promote oxidative stress and ROS activity than heavy resistance training.…”
Section: Redox Potentialmentioning
confidence: 99%
“…Indeed, while Koechlin and coworkers (26) used submaximal, small-muscle mass exercise (dynamic knee extensions at 40% of the maximal voluntary contraction), the patients in the present study underwent an incremental, symptom-limited treadmill exercise test. These protocol differences are important because the effects of NAC on muscle fatigue appear to be task and intensity specific (16,29). In fact, marked improvements in muscle performance after NAC are particularly evident during small-muscle mass exercise at submaximal intensities (26,29).…”
Section: Nac and Walking Capacitymentioning
confidence: 99%
“…These protocol differences are important because the effects of NAC on muscle fatigue appear to be task and intensity specific (16,29). In fact, marked improvements in muscle performance after NAC are particularly evident during small-muscle mass exercise at submaximal intensities (26,29). Nonetheless, we chose treadmill testing instead of small-muscle mass exercise because treadmill walking mimics more closely what these patients experience in daily life (25).…”
Section: Nac and Walking Capacitymentioning
confidence: 99%